ChemInform Abstract: Synthesis, Crystal Chemistry, and Electrochemical Properties of Li7‐2xLa3Zr2‐xMoxO12 (x = 0.1—0.4): Stabilization of the Cubic Garnet Polymorph via Substitution of Zr4+ by Mo6+. Issue 3 (29th December 2015) - Rettenwander, Daniel; Welzl, Andreas; Cheng, Lei; Fleig, Juergen; Musso, Maurizio; Suard, Emmanuelle; Doeff, Marca M.; Redhammer, Guenther J.; Amthauer, Georg
Abstract: Li7‐2x La3 Zr2‐x Mox O12 (x = 0.1—0.4) are prepared by calcining a stoichiometric mixture of Li2 CO3, La2 O3, ZrO2, and MoO3 (850 °C, 4 h), followed by grinding and final sintering (1230 °C, 4 h).